2021
DOI: 10.3389/fphys.2021.760251
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Programming of Cardiovascular Diseases in Maternal Diabetes

Abstract: Maternal diabetes is a prevalent pathology that increases the risk of cardiovascular diseases in the offspring, the heart being one of the main target organs affected from the fetal stage until the adult life. Metabolic, pro-oxidant, and proinflammatory alterations in the fetal heart constitute the first steps in the adverse fetal programming of cardiovascular disease in the context of maternal diabetes. This review discusses both human and experimental studies addressing putative mechanisms involved in this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…In a Danish population-based cohort study, Yu et al reported that during a 40-year follow-up, offspring of mothers with pregestational diabetes had a hazard ratio (HR) of 1.29 to develop early onset CVD [ 6 ]. Although the exact mechanism remains unknown, the earliest signs of CVD could originate already in the developing fetus, possibly mediated through epigenetic mechanisms [ 21 ]. Murray et al reported that maternal risk factors during pregnancy could induce DNA methylation in the offspring’s genome at birth, which in turn, was found to be associated with enhanced arterial stiffening after a follow-up of 8–9 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Danish population-based cohort study, Yu et al reported that during a 40-year follow-up, offspring of mothers with pregestational diabetes had a hazard ratio (HR) of 1.29 to develop early onset CVD [ 6 ]. Although the exact mechanism remains unknown, the earliest signs of CVD could originate already in the developing fetus, possibly mediated through epigenetic mechanisms [ 21 ]. Murray et al reported that maternal risk factors during pregnancy could induce DNA methylation in the offspring’s genome at birth, which in turn, was found to be associated with enhanced arterial stiffening after a follow-up of 8–9 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is prevalent in the adult population and the leading cause of morbidity and mortality globally 1,2 . Pregnancy is a highly vulnerable period, where complications can influence maternal and fetal development, also potentially affecting future health in childhood and adulthood 3 . Atherosclerosis, a progressive disease characterized by the formation of lipid plaques in the arteries and the dominant cause of CVD, may begin during intrauterine life, with early lesion formation in fetal vessels associated with hypercholesterolemia during pregnancy, 3–9 adversely impacting later life.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Pregnancy is a highly vulnerable period, where complications can influence maternal and fetal development, also potentially affecting future health in childhood and adulthood. 3 Atherosclerosis, a progressive disease characterized by the formation of lipid plaques in the arteries and the dominant cause of CVD, may begin during intrauterine life, with early lesion formation in fetal vessels associated with hypercholesterolemia during pregnancy, 3 , 4 , 5 , 6 , 7 , 8 , 9 adversely impacting later life. Preeclampsia (PE) is considered a risk factor for CVD later in the life of the mother and the offspring; it often involves inadequate blood flow to the placenta, leading to hypoxia or reduced oxygen supply to the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse developmental programming is directly related to cardiovascular disease in later life. The epigenetic modifications that occur in response to intra-uterine alterations have lasting effects and are known to alter cardiovascular structure and function in response to several environmental factors and maternal behaviors [1][2][3][4][5] . One of the most detrimental maternal behaviors during the perinatal period, which can deleteriously predispose offspring to cardiovascular diseases, is nicotine exposure, typically in the form of tobacco product use 6 .…”
Section: Introductionmentioning
confidence: 99%